2008
DOI: 10.1098/rsif.2007.1327
|View full text |Cite
|
Sign up to set email alerts
|

Periodic travelling waves in cyclic populations: field studies and reaction–diffusion models

Abstract: Periodic travelling waves have been reported in a number of recent spatio-temporal field studies of populations undergoing multi-year cycles. Mathematical modelling has a major role to play in understanding these results and informing future empirical studies. We review the relevant field data and summarize the statistical methods used to detect periodic waves. We then discuss the mathematical theory of periodic travelling waves in oscillatory reactiondiffusion equations. We describe the notion of a wave famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(132 citation statements)
references
References 175 publications
(290 reference statements)
5
124
0
3
Order By: Relevance
“…The logistic equation, however, predicts only very simple dynamics, such as monotonic convergence to a steady state, and this is clearly at odds with the complexity of the dynamics observed in natural populations where sustained oscillations are much more typical (Ranta et al, 1995;Cushing et al, 2003;Turchin, 2003;Sherratt and Smith, 2008). This is of course hardly surprising, as the logistic equation obviously leaves many things out of focus; in particular, it assumes that offspring start reproducing the moment they are born and are born immediately after they are conceived.…”
Section: Discussionmentioning
confidence: 99%
“…The logistic equation, however, predicts only very simple dynamics, such as monotonic convergence to a steady state, and this is clearly at odds with the complexity of the dynamics observed in natural populations where sustained oscillations are much more typical (Ranta et al, 1995;Cushing et al, 2003;Turchin, 2003;Sherratt and Smith, 2008). This is of course hardly surprising, as the logistic equation obviously leaves many things out of focus; in particular, it assumes that offspring start reproducing the moment they are born and are born immediately after they are conceived.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, spatio-temporal dynamics compatible with trophic interactions, e.g. travelling waves, a form of spatial asynchrony likely to result from enemyvictim interactions (Sherratt & Smith 2008), have been reported to occur (e.g. Tenow et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…In that case, the spatial patterning of enemy-inflicted mortality should match with the pattern of victim population dynamics. However, Sherratt & Smith's (2008) review of spatiotemporal dynamics of cyclic populations due to trophic interactions found no examples of such studies. Here, we demonstrate how targeted field studies invoking spatial demographic data can be used to reject specific trophic mechanisms as decisive for the spatio-temporal dynamics of cyclic species, using geometrid moths in northern Fennoscandia as an example.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations